MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI MEDIA KARTU MAJEMUK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK PERMATA HATI BANGKINANG KOTA KECAMATAN BANGKINANG KABUPATEN KAMPAR - Eliana, Desi; Zulkifli, Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase ability to know the concept of numbers in children aged 4-5 years through the media card in TK Permata Hati Bangkinang City District Bangkinang regency of Kampar. This study is research using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. This research subject is a child is a child aged 4-5 years amounted to 15 children in kindergarten Permata Hati Bangkinang City. The research data obtained through observation and data analysis were performed quantitatively. The results showed the compound under media card can improve the ability to know the concept of children aged 4-5 years. It can be seen from the increase in the average percentage recognize the concept of numbers of children in the first cycle by 32, 77% are located in underdeveloped criteria (B B) and an increase of 84.77% in the second cycle be 60.55% which is at criteria developing according to expectations (BSH). So, media card compound can improve the ability to know the concept of the number of children aged 4-5 years in kindergarten Permata Hati Bangkinang City District Bangkinang regency of Kampar.Keywords : Know Your Numbers ability Concepts, Methods Media Card Compound